Anterior interosseous nerve syndrome following paediatric supracondylar humeral fracture : a case report: Sindorm anteriornega intraosalnega živca pri otroškem suprakondilarnem prelomu nadlaktnice - prikaz primera - Pevec, Teodor; Kalšek, Simonca; Majerič, Mihael (Acta Medico-Biotechnica, 2021)
Purpose: The anterior interosseous nerve (AIN) is a motor branch of the median nerve that runs deep into the forearm where it innervates three muscles. Their isolated palsy is known as AIN syndrome. Distal forearm fractures are some of the most common fractures in children and are associated with frequent neurovascular complications. This report described a relatively rare complication in our everyday medical practice: AIN syndrome following a supracondylar fracture. Case report: A 5-year-old boy fell off of a swing and suffered a supracondylar fracture. No neurological disorders were described. Manual reduction and K-wire fixation were performed. At a follow-up visit, the mother pointed out that the child was unable to flex the thumb of the treated arm. We diagnosed the case as AIN syndrome. Conclusion: The AIN syndrome was most likely a consequence of the injury to the elbow itself. Due to our focus on more frequent neurological disorders, especially those of the ulnar nerve, AIN syndrome was detected relatively late. In preoperative care, and especially postoperative care of children with distal forearm fractures, precise assessments of the patient’s neurological status are required for the early detection of associated injuries.